2013 2nd Mediterranean Conference on Embedded Computing (MECO) 2013
DOI: 10.1109/meco.2013.6601327
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of filtering efficiency for DCT-based image denoising

Abstract: The task of prediction practical efficiency of filtering on the basis of the discrete cosine transform (DCT) methods is considered. It is shown that it is possible to estimate the MSE values of images to be processed by means of calculation rather simple statistics of DCT coefficients. Moreover, the quasi-optimal value of threshold parameter for DCT filtering methods can be easy evaluated as well. The results are presented for different additive Gaussian noise levels and a set of gray-scale test images.Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 15 publications
0
40
0
5
Order By: Relevance
“…Secondly, it has been already demonstrated that IPSNR for many¯lters can be predicted quite accurately for DCT-based¯lters 1,33,38,51 and some other denoising techniques. 34 Accuracy can be characterized di®erently where the root mean square error (RMSE) of estimates is one of the most adequate and widely used quantitative criteria.…”
Section: Filtering E±ciency Predictionmentioning
confidence: 96%
See 2 more Smart Citations
“…Secondly, it has been already demonstrated that IPSNR for many¯lters can be predicted quite accurately for DCT-based¯lters 1,33,38,51 and some other denoising techniques. 34 Accuracy can be characterized di®erently where the root mean square error (RMSE) of estimates is one of the most adequate and widely used quantitative criteria.…”
Section: Filtering E±ciency Predictionmentioning
confidence: 96%
“…An idea that such indicators of denoising e±ciency can be predicted (estimated before image denoising is applied) has been put forward in papers. 1,8 The way proposed in Ref. 8 requires considerable computations and, thus, the time needed to derive a prediction indicator is comparable to a¯ltering procedure itself that restricts the practical application of this approach.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Suppose we have a method (procedure) that allows predicting filtering efficiency and deciding in advance (before starting filtering) whether it is worth applying filtering or not [14,15]. If such a method (procedure) is fast (performs considerably faster than filtering itself) and is accurate enough, it can be a useful tool in image processing (especially for hardware or software operating in automatic or semi-automatic mode) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some steps towards designing prediction procedures have been done [15,[17][18][19][20][21]. In [17], it has been shown that for non-local denoising methods applied to remove additive white Gaussian noise (AWGN) it is possible to predict potential output mean square error (MSE) without having the corresponding reference image.…”
Section: Introductionmentioning
confidence: 99%